PERILAKU INFORMASI CONTENT CREATOR JEJARING SOSIAL BERBASIS VIDEO - Aypa Berhama Zega, Derin; Safii, Moh.; Roekhan (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2022)
Information search is carried out by all groups to support their daily work. This is also done by content creators as content creators so that the content shared is accurate and useful. This study aims to describe the information behavior of content creators using David Ellis' information behavior model. This research is a type of qualitative research. Data collection techniques with interviews and documentation studies. Sampling in the study was selected through a purposive sampling technique. Through this technique, two people were chosen to act as content writers and editors as informants in this study because they were directly involved in developing story ideas and writing video scripts for the